2009
DOI: 10.1148/radiol.2503080875
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis: Contrast-enhanced MR Imaging of Vessel Wall in Rabbit Model—Comparison of Gadofosveset and Gadopentetate Dimeglumine

Abstract: http://radiology.rsnajnls.org/cgi/content/full/250/3/682/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 27 publications
3
31
1
Order By: Relevance
“…Indeed, extravascular albumin has been detected in both human and mouse atherosclerotic lesions. 38,39 Here, we extend these findings, demonstrating an apparent size limit for endothelial leakage in vasa vasorum of 70 to 150 kDa in vivo in aged ApoE −/− mice. The origin of the microvascular hyperpermeability remains to be further elucidated.…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, extravascular albumin has been detected in both human and mouse atherosclerotic lesions. 38,39 Here, we extend these findings, demonstrating an apparent size limit for endothelial leakage in vasa vasorum of 70 to 150 kDa in vivo in aged ApoE −/− mice. The origin of the microvascular hyperpermeability remains to be further elucidated.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies suggested that extravasation of gadofosveset in experimental 32 and human atherosclerosis 33 occurs through leaky microvessels. However, in these studies, a detailed analysis of the endothelium was not performed.…”
Section: Discussionmentioning
confidence: 97%
“…[27][28][29] Gadofosveset is a clinically approved gadolinium-based contrast agent that reversibly binds to serum albumin, resulting in a prolonged vascular presence and a 5-to 10-fold increase in relaxivity (r 1 ). 30,31 Gadofosveset is predominantly present within the vessel lumen but may enter the vessel wall through leaky neovessels 32,33 and mechanically damaged endothelium. 34 Although it has long been known that endothelial dysfunction is the primary event in atherogenesis, noninvasive assessment of endothelial permeability has not yet been established in vivo.…”
Section: Clinical Perspective On P 719mentioning
confidence: 99%
“…Studies using clinically approved extracellular contrast agents showed that uptake in the coronary artery wall is non-specific and could be associated with both atherosclerotic plaque composition and inflammation in patients with stable CAD or acute coronary syndrome [80,81]. Enhancement with newly developed albumin binding and iron oxide-based contrast agents is associated with increased endothelial permeability and thus can be used for coronary wall imaging [82][83][84][85].…”
Section: Coronary Artery Wall Imagingmentioning
confidence: 99%